Farmer-led conservation of paddy landraces in Western Odisha (Indian Journal of Traditional Knowledge (IJTK), 2024)
Despite the Green Revolution's impact, many small-scale farmers continue cultivating landraces for their agronomic, culinary, and cultural values. This study, conducted in Odisha, focuses on region-specific on-farm conservation practices employed by farmers for landraces. Five focused group discussions were conducted in five villages, involving 15 landrace custodian farmers in each village of Western districts of Odisha. The Four-Square Analysis, a participatory approach, was utilized to evaluate landrace conservation practices in five villages. Principal Component Analysis and Biplot visualization were employed to analyze the relationships between practices, varieties, and conservation scores. Focused group discussion revealed that a total of 30 paddy landraces were cultivated and conserved in the sampled villages. The study identified diverse landraces such as Kalabati, Katia, and Kusum kali, each valued for unique traits and cultural significance. Paddy landraces with disease resistance, medicinal value, and economic significance were commonly cultivated in households or on a larger scale. Important agronomic practices involved organic farming, reduced fertilizer use, biological pest control, System of Rice Intensification (SRI), and bacterial culture for landrace conservation. Management practices comprised seed banks, diversity blocks, seed exchanges, and community cultivation. The findings highlight the importance of farmers' indigenous knowledge, their beliefs and cultural practices in conserving landraces. Landraces which were rare and cultivated due to cultural or social importance require special attention in conservation efforts. Incentivizing community involvement and implementing tailored strategies would be crucial for effective landrace conservation initiatives.